The Role of Maternal Knowledge, Family Support, and Access to Health Services on The Success of Complete Basic Immunization - Maria Ulfah Jamil; Nina Nahdriah; Asep Mulyana; Fitriani Mardiana (Nurul Ilmi : Journal of Health Sciences and Midwifery, 2026)
Introduction: Complete basic immunization is an important effort in preventing infectious diseases in infants; however, its coverage is still not optimal. Nationally, the coverage of complete basic immunization in Indonesia continues to fluctuate and has not yet reached the established targets, mainly due to various barriers such as limited public knowledge, inadequate family support, and restricted access to health services. This condition indicates the need for more targeted efforts to improve the success of immunization programs. Objective: The purpose of this study is to determine the role of maternal knowledge, family support, and access to health services in the success of complete basic immunization in the working area of Sukalaksana Public Health Center, Tasikmalaya City. Method: The method used in this study is a quantitative approach with an analytical observational design using a cross-sectional approach. The population in this study consists of mothers who have infants aged 9–12 months, with a total sample of 92 respondents selected using a simple random sampling technique. Result: The results of this study show that the majority of respondents have good knowledge (54.3%), receive family support (65.2%), and have easy access to health services (63.0%). A total of 67.4% of infants have received complete basic immunization. The bivariate analysis indicates a significant relationship between maternal knowledge (p = 0.012), family support (p = 0.001), and access to health services (p = 0.004) with the success of complete basic immunization. Conclusion: Based on the results of the study, maternal knowledge, family support, and access to health services play an important role in improving the success of complete basic immunization.